Safety Related Issues of Spent Nuclear Fuel Storage - Lambert, J.D.B.; Kadyrzhanov, K.K.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2007)
At a NATO-sponsored workshop in Almaty in September 2005, specialists from the IAEA, Brazil, France, Kazakhstan, Poland, Russia, USA and Uzbekistan discussed safety-related issues of storing spent nuclear fuel. Fifteen papers dealt with aluminium-clad fuel discharged from research reactors worldwide, five papers were concerned with stainless steel-clad fuel from fast reactors, and two were devoted to Zircaloy-clad fuel from commercial light-water reactors. Although most attention was focused on fuel behaviour in storage pools, many countries—through lack of space—are beginning to ‘dry store’ spent fuel in an inert atmosphere in shielded casks, and both topics were covered thoroughly at the workshop. Water quality and dryness of the spent fuel, respectively, are the critical factors in avoiding material degradation for the two storage modes. No burning safety-related issue emerged from the twenty-two papers presented; however, the lack of wet storage space at most reactors and concerns regarding possible sabotage remain as issues that need to be periodically addressed.
Strategies for Safe Storage of Spent Fuel -- Spent Nuclear Fuel from Research Reactors: International Status and Perspectives -- Regulatory Approach for Managing Radioactive Waste in the Republic of Kazakhstan -- Spent Fuel Management in Poland -- An Overview of Spent Fuel Storage at Commercial Reactors in the United States -- Managing Spent Nuclear Fuel at the Idaho National Laboratory -- Radiological Problems of Spent Fuel Storage -- Assessment of Environmental Impact of Reactor Facilities in Kazakhstan -- Design and Manufacture of Fuel Assemblies for Russian Research Reactors -- Strategy for Handling Spent BN-350 Cesium Traps in the Republic of Kazakhstan -- Account and Control of Nuclear Materials at the WWR-SM Reactor in the Institute of Nuclear Physics, Tashkent -- Activities of the Kharkov Institute Related to the Problem of Spent Nuclear Fuel Management -- Technical Issues of Wet and Dry Storage -- Understanding and Managing the Aging of Spent Fuel and Facility Components in Wet Storage -- Long-Term (100–300 Years) Interim Dry Storage for Spent Fuel: Package and Facilities Development Including Safety Aspects and Durability Assessment Program -- Technical Issues of Wet and Dry Storage Facilities for Spent Nuclear Fuel -- Problems of Nuclear and Radiation Safety of Casks with Spent Fuel during Long-Term Dry Storage -- Trial of Storage Container Technology for Research Reactor Spent Nuclear Fuel -- Interim Storage and Long-Term Disposal of Research Reactor Spent Fuel in the United States -- Materials Stability Issues of Spent Fuel Storage -- Managing Spent Fuel in Wet Storage at the Savannah River Site -- Corrosion of Aluminium Alloy SAV-1 and Austenitic Stainless Steels 12Cr18Ni10Ti and 08Cr16Ni11Mo3—Core Structural Materials for WWR-K and BN-350 Reactors -- Corrosion of Fast-Reactor Claddings by Physical and Chemical Interaction with Fuel and Fission Products -- Corrosion of Research Reactor Aluminum Clad Spent Fuel in Wet Storage -- Influence of Neutron Irradiation on Mechanical and Dimensional Stability of Irradiated Stainless Steels and its Possible Impact on Spent Fuel Storage -- Degradation in Mechanical Properties of Stainless Steels C0.12Cr18Ni10Ti and C0.08Cr16Ni11Mo3—Materials for Hexagonal Ducts of Spent Fuel Assemblies from the BN-350 Fast Neutron Reactor.
Keywords: Materials science; Energy systems; Tribology; Corrosion and anti-corrosives.; Coatings; Metals; Nuclear energy; Materials Science, general; Energy Systems; Tribology, Corrosion and Coatings; Metallic Materials; Nuclear Energy